Analisis Sistem Akuntansi Masjid As Sulthan Kabupaten Sarolangun - Nazori Majids; Lidya Anggraeni; Nadiatul Khoriah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
Accounting information system is a system that aims to collect and process data and report information related to financial transactions. The mosque accounting system is the process of identifying, measuring, recording, and reporting financial transactions carried out by mosques as a form of accountability in managing mosque resources. The purpose of this study is to analyze the As Sulthan Mosque in Sarolangun Regency has not implemented an accounting system in its financial statements, to find out the accounting principles that have been applied by the As Sulthan Mosque, Sarolangun Regency, and to determine the accountability of financial management at the As Sulthan Mosque, Sarolangun Regency. This research is a qualitative research with the number of informants in this study is 5 people. The results showed that 1) As Sulthan Mosque in Sarolangun Regency had not implemented financial reports according to PSAK 45 Standards because As Sulthan Mosque in Sarolangun Regency was due to a lack of Human Resources who understood the applicable Financial Accounting Standards and the absence of experts with educational backgrounds in Accounting field. 2) 75% of the accounting principles that have been applied by Masjid As Sulthan, Sarolangun Regency, are 6 (six) principles applied from 8 (eight) existing principles. 3) Accountability of financial reports carried out by the As Sulthan Mosque, Sarolangun Regency by pasting its operational financial reports on the wall magazine, and announced when they will perform Friday prayers